2022
DOI: 10.3389/fnins.2022.855955
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Gait Speed and Sleep Problems Among Chinese Adults Aged 50 and Greater

Abstract: ObjectiveThe relationship between sleep problems and walking speed has been less explored. The present cross-sectional study was to investigate the association between sleep quality and sleep duration and gait speed in Chinese adults.MethodsA total of 13,367 participants were recruited in this cross-sectional study, retrieving the data from the Global Aging and Adult Health Survey (SAGE). Gait speed was measured using the 4-m walking test. Age, sex, education years, smoking status, alcohol consumption, physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In children, it appears that the worst dual-task performance is associated with disrupted sleep, a higher quantity of REM (rapid eye-movement) sleep related to lower gait variability, and a higher cognitive performance associated with a greater quantity of slow-wave sleep [ 54 ]. Another study showed that poor sleep quality was related with a slower normal walking speed in adults [ 31 ]. In addition, a decrease in gait speed and higher gait variability were associated with a lower sleep efficiency during a dual-task but not while performing a single task in older people [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In children, it appears that the worst dual-task performance is associated with disrupted sleep, a higher quantity of REM (rapid eye-movement) sleep related to lower gait variability, and a higher cognitive performance associated with a greater quantity of slow-wave sleep [ 54 ]. Another study showed that poor sleep quality was related with a slower normal walking speed in adults [ 31 ]. In addition, a decrease in gait speed and higher gait variability were associated with a lower sleep efficiency during a dual-task but not while performing a single task in older people [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies suggest that the oxyhemoglobin was higher after a whole night’s sleep than at the beginning of the night [ 25 ]. Others reported that sleep plays an important role in the processes of learning and memory [ 26 ], that physical activity benefits the executive function [ 27 ] and gait speed [ 28 ], and that sedentarism [ 29 ], poor sleep quality [ 30 ], and more than 8 h of sleep duration [ 31 ] can be associated with lower gait speed.…”
Section: Introductionmentioning
confidence: 99%